2007
DOI: 10.1177/0013124507302396
|View full text |Cite
|
Sign up to set email alerts
|

School—Police Partnership Effectiveness in Urban Schools: An Analysis of New York City's Impact Schools Initiative

Abstract: Despite nationwide decreases in school crime and violence, a relatively high and increasing number of students report feeling unsafe at school. In response, some school officials are implementing school—police partnerships, especially in urban areas, as an effort to deter criminal activity and violence in schools. This article examines the initial effect of New York City's Impact Schools Initiative, a punitive-based school—police partnership developed in January 2004 that increases police presence at some of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 19 publications
3
45
0
1
Order By: Relevance
“…Although findings across the two survey sources were not entirely convergent, taken together, they provide no evidence that visible security measures have consistent beneficial effects on adolescents' academic outcomes, and indeed, that certain security utilization patterns may have modest detrimental effects on academic outcomes (even after controlling for a range of other potential confounding variables). Overall, these results are consistent with prior evidence that visible security measures, particularly the presence of security personnel, may be negatively related to adolescents' academic performance and/or attendance (Brady et al 2007). Although this study focused specifically on outcomes related to adolescents' academic outcomes, these results parallel recent findings that indicate visible security measures may also be related to worse student behavior outcomes such as delinquency and victimization (Na and Gottfredson 2013;Tanner-Smith et al 2015) In the administrator-reported survey data, most of the observed detrimental effects on adolescents' academic outcomes were driven by a small group of roughly 100 schools that utilized all three types of security measures.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Although findings across the two survey sources were not entirely convergent, taken together, they provide no evidence that visible security measures have consistent beneficial effects on adolescents' academic outcomes, and indeed, that certain security utilization patterns may have modest detrimental effects on academic outcomes (even after controlling for a range of other potential confounding variables). Overall, these results are consistent with prior evidence that visible security measures, particularly the presence of security personnel, may be negatively related to adolescents' academic performance and/or attendance (Brady et al 2007). Although this study focused specifically on outcomes related to adolescents' academic outcomes, these results parallel recent findings that indicate visible security measures may also be related to worse student behavior outcomes such as delinquency and victimization (Na and Gottfredson 2013;Tanner-Smith et al 2015) In the administrator-reported survey data, most of the observed detrimental effects on adolescents' academic outcomes were driven by a small group of roughly 100 schools that utilized all three types of security measures.…”
Section: Discussionsupporting
confidence: 89%
“…Although there has been increased federal funding for school security measures in recent years (The White House 2013), there is a notable lack of rigorous empirical research that has examined the effects of visible security measures on adolescents' academic success (Addington 2009;Fletcher et al 2008;Hankin et al 2011). Among the few studies that have examined how visible school security measures are associated with adolescents' academic success, findings have been inconsistent, including positive effects (Link 2010), negative effects (Brady et al 2007), or no evidence of an effect (Coon 2004;Peguero and Bracy 2015;Rogers 2004). However, most prior research studies have focused on only one type of security measure at a time (e.g., security personnel), have failed to explore possible moderators of any observed effects, and/or used weak correlational research designs that do not permit causal inferences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, there had to be clear evidence that at least one SRO (not a non-SRO police officer or private security guard) was present at the school. The models of involvement of non-SRO security personnel in schools are often quite different from those of SROs (see, for example, Brady et al 2007). Third, the report had to provide information for analytical comparison.…”
Section: Methods Eligibility Criteriamentioning
confidence: 99%
“…Whereas police and security officers in schools were not new phenomenon, school resource officers within schools had become the fastest growing law enforcement field (Brady, Balmer, & Phenix, 2007). School resource officers in schools received training specific to educational settings.…”
Section: Introductionmentioning
confidence: 99%